2017
DOI: 10.1111/gcb.13785
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic soil fungi enhance ecosystem resilience to climate change

Abstract: Substantial amounts of nutrients are lost from soils through leaching. These losses can be environmentally damaging, causing groundwater eutrophication and also comprise an economic burden in terms of lost agricultural production. More intense precipitation events caused by climate change will likely aggravate this problem. So far it is unresolved to which extent soil biota can make ecosystems more resilient to climate change and reduce nutrient leaching losses when rainfall intensity increases. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…In terrestrial soils, fungi are often associated with a higher C‐use efficiency and a lower nutrient demand than bacteria (van der Heijden, Bardgett, & Straalen, ; Strickland & Rousk, ), and thus, nutrient cycles are supposed to become increasingly closed (i.e., less leaky) and C turnover to slow down with increasing relative fungal abundance (Martínez‐García, Deyn, Pugnaire, Kothamasi, & van der Heijden, ; Moore et al, ; de Vries, Hoffland, Eekeren, Brussaard, & Bloem, ; Wardle, Bardgett, et al, ; Wardle, Walker, & Bardgett, ). The here presented increase in fungal abundance along the elevation gradient might therefore reflect that nutrient cycles in tidal wetlands become increasingly closed with decreasing flooding frequency and thus external nutrient input (Schrama, Jouta, Berg, & Olff, ; Van Wijnen & Bakker, ).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial soils, fungi are often associated with a higher C‐use efficiency and a lower nutrient demand than bacteria (van der Heijden, Bardgett, & Straalen, ; Strickland & Rousk, ), and thus, nutrient cycles are supposed to become increasingly closed (i.e., less leaky) and C turnover to slow down with increasing relative fungal abundance (Martínez‐García, Deyn, Pugnaire, Kothamasi, & van der Heijden, ; Moore et al, ; de Vries, Hoffland, Eekeren, Brussaard, & Bloem, ; Wardle, Bardgett, et al, ; Wardle, Walker, & Bardgett, ). The here presented increase in fungal abundance along the elevation gradient might therefore reflect that nutrient cycles in tidal wetlands become increasingly closed with decreasing flooding frequency and thus external nutrient input (Schrama, Jouta, Berg, & Olff, ; Van Wijnen & Bakker, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi may promote drought recovery in plants, and resist decoupling (Fuchslueger et al, 2014), by extending the root network of plants and improving access to water and nutrients post-rewetting through hydraulic relocation, mycelia networks, and hyphae of both saprotrophic and AM fungi (Guhr, Marzini, Borken, Poll, & Matzner, 2016;Lau & Lennon, 2012;Wardle et al, 2004). In addition, grasslands with a high abundance of fungi have been shown to maintain larger soil nutrient pools during drying-rewetting periods (Gordon et al, 2008;Martínez-García, De Deyn, Pugnaire, Kothamasi, & van der Heijden, 2017). Shifts in plant-soil feedbacks and/or competition for N, which increase plant N uptake in the presence of fungi, may further enhance plant recovery after drought (Kaisermann, de Vries, Griffiths, & Bardgett, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Asghari and Cavagnaro found that the inoculation of AM fungi in Phalaris aquatica L. significantly reduced the leaching of both NO 3 − and NH 4 + [23]. It has also been reported that less mineral N [24], dissolved organic N [25], and total dissolved N [26] are leached under AM fungi treatment. The above results indicate that the impacts of AM fungi on N leaching are variable and may depend on the host plant species [27], AM fungal species [28], N application rate [29], the form of N fertilizer [25], the water regime [21], and the soil type [25].…”
Section: Introductionmentioning
confidence: 93%
“…Most of the related articles have reported that the higher capacity of mycorrhizal root systems to reduce NO 3 − -N leaching could be partly attributed to the larger size and the higher plant N content of mycorrhizal plants [20,21,23], demonstrating that AM enhanced the capacity of plants to acquire N. Furthermore, AM fungi indirectly influenced N leaching through shifting the plant community structure. For example, Martínez-García observed that with increased abundance of forbs and legumes, and decreased abundance of grasses in the presence of AM fungi, N leaching was reduced, especially when rainfall intensity increased [24]. AM fungi might promote the soil microbial communities that immobilized N more efficiently, thus enhancing microbial biomass N content and thereby increasing NH 4 + and dissolved organic N retention [25].…”
Section: Introductionmentioning
confidence: 99%